2020
DOI: 10.1186/s12887-020-02189-4
|View full text |Cite
|
Sign up to set email alerts
|

A 8- year Bangladeshi girl with disseminated histoplasmosis, presented as chronic liver disease with portal hypertension: a rare case report

Abstract: Background Histoplasmosis is a rare infectious condition with mainly pulmonary involvement. Disseminated histoplasmosis may occur in immunocompromised condition. It can present in different ways but jaundice and ascites is very uncommon. Case presentation A 8- year old girl visited to department of pediatric gastroenterology & nutrition, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Child presented with fever, j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Symptoms include fever, malaise, weight loss, cough, and diarrhea. On physical examination, most patients are found to have hepatosplenomegaly, lymphadenopathy, and pulmonary crackles [ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms include fever, malaise, weight loss, cough, and diarrhea. On physical examination, most patients are found to have hepatosplenomegaly, lymphadenopathy, and pulmonary crackles [ 1 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Around 90% of patients have anemia, and 80% of affected children present with leucopenia and thrombocytopenia. Patchy infiltrates with mediastinal and hilar lymph node enlargement are frequently found on chest X-rays [ 1 , 17 ]. When the liver is affected, although transaminases may be elevated, high levels of alkaline phosphatase (≥2100 U/L) are one of the most prominent biochemical laboratory findings [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few case reports of liverbiopsy-proven histoplasmosis have reported associated cholestasis. 25,[28][29][30] The typical clinical presentations are fever and jaundice in the setting of immunosuppression. Right upper quadrant pain might be confused with biliary colic in cases of cholestatic hepatitis secondary to disseminated histoplasmosis.…”
Section: Hepatic Histoplasmosismentioning
confidence: 99%
“…20 Two case reports by Park et al 24 and Kothadia et al 30 describe patients who underwent laparoscopic cholecystectomy for uncertain etiology shortly before being diagnosed with disseminated histoplasmosis. Nahar et al 28 reported a patient with disseminated histoplasmosisthat presented as chronic liver disease with portal hypertension.…”
Section: Hepatic Histoplasmosismentioning
confidence: 99%